2012
DOI: 10.4103/1319-3767.93825
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of colchicine in the treatment of mesenteric panniculitis in a young patient

Abstract: Mesenteric panniculitis (MP) is a rare inflammatory and fibrotic disease of the mesentery of unknown etiology. It has various clinical and radiological manifestations, posing a diagnostic challenge for clinicians. Its diagnosis is indicated via radiologic imaging and is usually confirmed via peritoneal biopsies. We describe a case of a patient with histopathologically proven MP, in which steroid dependence was successfully managed with colchicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The patient was subsequently treated with pentoxifylline, with substantial clinical and radiological improvements [ 42 ]. Fasoulas et al reported a case of MP in whom steroid dependence was successfully managed with colchicine without any recurrence [ 43 ]. R Mazure et al described a patient with MP refractory to surgery who achieved a good response to oral progesterone (10 mg/day for 6 months) with complete disappearance of tumor mass and clinical symptoms [ 44 ], which might be associated with their fibrinolytic characteristics [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patient was subsequently treated with pentoxifylline, with substantial clinical and radiological improvements [ 42 ]. Fasoulas et al reported a case of MP in whom steroid dependence was successfully managed with colchicine without any recurrence [ 43 ]. R Mazure et al described a patient with MP refractory to surgery who achieved a good response to oral progesterone (10 mg/day for 6 months) with complete disappearance of tumor mass and clinical symptoms [ 44 ], which might be associated with their fibrinolytic characteristics [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“… 9 In case of poor improvement of symptoms, the second line therapy to be adopted includes the association between prednisone and azathioprine 2–2.25 mg/kg daily or simply thalidomide 200 mg daily. 9 Other medical drugs used successfully, but less frequently, in different case reports are colchicine, 25 6-mercaptopurine, 26 methotrexate, 27 cyclophosphamide 28 and infliximab. 29 Surgery is reserved only in patients with complications, such as bowel obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with sclerosing mesenteritis have an uneventful course and the symptoms resolve spontaneously[3]. Several therapeutic approaches with agents such as steroids, colchicine and azathioprine have been described with various therapeutic effects[16-18]. In cases of non-resolving bowel obstruction or an advanced inflammatory reaction, surgical resection of the inflamed fat may be necessary[1,12].…”
Section: Discussionmentioning
confidence: 99%